2020
DOI: 10.1186/s12889-020-8207-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of metabolic syndrome in adults: a population-based epidemiological survey in Jiangxi province, China

Abstract: Background: Metabolic syndrome (MS) has abruptly increased in China in the past two decades, gradually representing an important public health threat over the years. Here, we firstly reported the prevalence and associated factors of metabolic syndrome in Jiangxi province, China. Methods: A population-based cross-sectional survey was performed in Jiangxi province, China, from April to August 2015. MS was diagnosed by International Diabetes Federation (IDF) and Chinese Diabetes Society (CDS) criteria, respective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 27 publications
6
19
2
9
Order By: Relevance
“…These findings were not observed among men. 42 In our study, MS was negatively associated with living in rural regions (OR: 0.74 (0.56 to 0.97), p=0.028) but not with living in urban regions. The differences may be caused by the degree of economic development, lifestyle habits and dietary patterns; for example, rural women have lower fat intake and more activity than urban women.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…These findings were not observed among men. 42 In our study, MS was negatively associated with living in rural regions (OR: 0.74 (0.56 to 0.97), p=0.028) but not with living in urban regions. The differences may be caused by the degree of economic development, lifestyle habits and dietary patterns; for example, rural women have lower fat intake and more activity than urban women.…”
Section: Discussioncontrasting
confidence: 41%
“…The percentage of included women with a primary school education or below was 37.8%, which may partially explain the high prevalence of MS in women. 24 Urban adults (≥18 years old) in China were more likely than rural adults to have MS in 2009, 22 The opposite was true among urban adults in Jiangxi province, China in 2015, as women living in rural areas were more likely than urban females to have MS. These findings were not observed among men.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MetS has increased in recent decades around the world and has reached an alarming level as it is a major public health and clinical concern [ 11 ]. In West and Asian populations, cardiovascular morbidity and mortality are two to five folds higher in people with this syndrome [ 12 14 ]. In a systematic review and meta-analysis study, the prevalence of metabolic syndrome in Iran according to ATPIII and IDF was reported 36.9% and 34.6%, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Так, распространенность МС наиболее низкая в Китае (15,2-21,1% населения) [18] и на Филиппинах (11,9%) [13], в то время как среди населения США данный показатель составляет 34,2% [19]. В Российской Федерации (РФ) МС встречается в диапазоне 40,3% -50,5% [1].…”
Section: факторы обусловливающие распространенность метаболического синдромаunclassified
“…В большинстве исследований сообщалось о более высокой распространенности МС у женщин [6,13]. Так, распространенность МС в Китае составила 17,1-19,6% среди мужчин и 13,0%-22,7% среди женщин [18]. У жительниц Индонезии данный показатель превышает заболеваемость МС среди лиц мужского пола (46% и 28% соответственно) [24].…”
Section: факторы обусловливающие распространенность метаболического синдромаunclassified